The Effect of Human Immunodeficiency Virus and Cytomegalovirus Infection on Infant Responses to Vaccines: A Review - Falconer, Olivia; Newell, Marie-Louise; Jones, Christine E. (Frontiers in Immunology, 2018)
The success of prevention of mother to child transmission programmes over the last two decades has led to an increasing number of infants who are exposed to human immunodeficiency virus (HIV), but who are not themselves infected (HIV-exposed, uninfected infants). Although the morbidity and mortality amongst HIV-exposed, uninfected infants is considerably lower than that amongst HIV-infected infants, they may remain at increased risk of infections in the first two years of life compared to their HIV-unexposed peers, especially in the absence of breastfeeding. There is some evidence of immunological differences in HIV-exposed, uninfected infants, which could play a role in susceptibility to infection. Cytomegalovirus (CMV) may contribute to the increased immune activation observed in HIV-exposed, uninfected infants. Infants born to HIV-infected women are at increased risk of congenital CMV infection, as well as early acquisition of postnatal CMV infection. In infants with HIV infection, CMV co-infection in early life is associated with higher morbidity and mortality. This review considers how HIV infection, HIV-exposure and CMV infection affect infant responses to vaccination, and explores possible immunological and other explanations for these findings. HIV-infected infants have lower vaccine-induced antibody concentrations following tetanus, diphtheria, pertussis, hepatitis B and pneumococcal vaccination, although the clinical relevance of this difference is not known. Despite lower concentrations of maternally-derived specific antibody at birth, HIV-exposed, uninfected infants respond to vaccination at least as well as their HIV-unexposed uninfected peers. CMV infection leads to an increase in activation and differentiation of the whole T-cell population, but there is limited data on the effects of CMV infection on infant vaccine responses. In light of growing evidence of poor clinical outcomes associated with CMV infection in HIV-exposed, uninfected infants, further studies are particularly important in this group. A clearer understanding of the mechanisms by which maternal viral infections influence the developing infant immune system is critical to the success of maternal and infant vaccination strategies.